WHAT MATTERS MOST: A PILOT STUDY TO DEVELOP QUALITY MEASURES FOR OLDER ADULTS WITH COMPLEX NEEDS. (11th November 2018) - Giovannetti, E; Sandberg, S; Angelia, B; Baird, S; Clair, C; Scholle, S
Abstract: Healthcare quality measures aim to evaluate providers and health plans so that consumers can make informed decisions on aspects of quality that matter most to them. Yet, most existing quality measures are based on a narrow set of health outcomes and do not effectively evaluate outcomes that are important to individuals themselves. This "one-size-fits-all" approach to measurement is particularly misaligned when evaluating care for older adults with complex needs. This population—including those with functional limitations, comorbidities, or both—frequently requires services and supports that extend beyond traditional medical care, and choices about treatment options that require complicated calculations of tradeoffs. To address the need for quality measures that reflect what matters most to individuals, we tested two approaches to personalized goal setting: goal attainment scaling (GAS) and person-reported outcome measures (PROM). Across six organizations, 34 clinicians (including physicians, nurse practitioners, registered nurses, and social workers) piloted the approaches with 232 older adults (GAS n=184; PROM n=49). Results demonstrate that older adults articulated a range of personalized outcomes important to them but not captured through current quality measures. Quantitative analyses show that on average 73% of older adults in the study with follow-up achieved the personalized goal they had selected over six months, but also revealed variation in achievement rates across organizations (range: 56–100%). Qualitative results highlight that despite the greater initial perceived workload, providers and older adults preferred the individualized GAS approach to the more structured PROM approach. GAS proved feasible for quality measurement across diverse settings of care.